(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: satisfaction of pregnant women is closely related to integrated ANC services. Pregnant women as health service users expect optimal ANC services provided by community health centers so that this indirectly has an impact on improving the quality of health services. In 2023 the number of K1 services will be 73% and K4 will be 46 % Hikun Health Center. Objective: to determine the relationship between the quality of integrated ANC services and the satisfaction of pregnant women at the Hikun Community Health Center. Method: quantitative analytical survey with a cross-sectional approach, and the sampling technique used was accidental sampling, a technique for determining samples based on chance, where the number of samples obtained was 68 respondents, using an instrument in the form of a questionnaire, with chi square test analysis. Results: maternal age not at risk (20-35 years) was 57 (83.8%), gestation age 8 months was 34 (50%), housewife occupation was 33 (48.5%), primigravida was 41 (60.2 %), and secondary education as many as 38 (55.9%). The quality of integrated ANC services was in the good category at 33 (48.5%) and the satisfaction of pregnant women was in the satisfied category at 35 (51.5%). There is a relationship between the quality of integrated ANC services and the satisfaction of pregnant women at the Hikun Health Center (p.value=0.000<0.05). Conclusion: satisfaction with the service will influence the mother’s visit to come back to have her womb checked, conversely, if the service does not provide a feeling of comfort, then the mother will not come back for an examination.